The Effect of Spindle Speed Variation on Results of Drilling Process in Radial Arm Drilling Machine RD-1600 - Calvin Aidil Febri; Ujang Nuhadek (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2019)
Radial Arm Drilling is a tool used to perforate an object. Radial Arm Drilling is designed for large work and work where the workpiece does not allow rotating. This machine consists of a vertical pole which supports an arm carrying a drill head. Its arms can rotate around to any position on the workbench, and the drill head has an adjustment along this arm. This radial arm drilling machine has automatic feeding, so in the drilling process, the operator no longer needs to press the spindle to the workpiece. The selection of feeding on the radial arm drilling machine is in accordance with the size of the drill bit used on the material to be drilled. For the selection of spindle, speed rotation has 2 types, namely high (50 hz and 60 hz) and low (50 hz and 60 hz).